\(a^2+ab+b^2=a^2b^2\)
\(\Rightarrow a^2+2ab+b^2=\left(ab\right)^2+ab\)
\(\Rightarrow\left(a+b\right)^2=ab\left(ab+1\right)\)
Vì (a+b)2 là số chính phương, mà ab(ab+1) là tích của 2 số nguyên liên tiếp nên dấu "=" xảy ra khi 1 trong 2 số bằng 0
\(\Rightarrow\left[{}\begin{matrix}ab=0\\ab=-1\end{matrix}\right.\)
\(\circledast ab=0\)
\(\Rightarrow\left(a+b\right)^2=0\)
\(\Rightarrow a+b=ab=0\)
\(\Rightarrow a=b=0\)
\(\circledast ab=-1\)
\(\Rightarrow\left\{{}\begin{matrix}a+b=0\\ab=-1\end{matrix}\right.\)
=> a = 1; b = -1 và hoán vị
Vậy,...............................................